Emerging sexually transmitted viral infections: 1. Review of Ebola virus disease. (November 2017) - Caswell, Rachel J; Manavi, Kaveh
This is the first in a series of articles reviewing four viral infections, Ebola virus, Zika virus, human T-cell lymphotropic virus, type 1 and hepatitis C virus, with an emphasis on recent advances in our understanding of their sexual transmission. With current day speed and ease of travel it is important for staff in sexual healthcare services to know and understand these infections when patients present to them and also to be able to advise those travelling to endemic regions. Following the recent resurgence in West Africa, this first article looks at Ebola virus disease (EVD). EVD has a high mortality rate and, of note, has been detected in the semen of those who have cleared the virus from their blood and have clinically recovered from the disease. As the result of emerging data, the WHO now recommends safe sex practices for all male survivors of EVD for 12 months after the onset of the disease or after having had two consecutive negative tests of semen specimens for the virus. This review provides an up-to-date summary of what is currently known about EVD and its implications for sexual health practice.